Editors' Introduction: A Reflective Report, of Sorts. - Davis, Matthew; Taczak, Kara (College Composition & Communication, 2026)
The article focuses on the editors' first-year reflection on stewarding College Composition and Communication, highlighting efforts to reduce review backlogs, stabilise workflows, launch special issues and new genres, and strengthen the journal's visibility and community engagement. It outlines their plans for year two, including expanding multimodal and visual scholarship and refining editorial processes in collaboration with National Council of Teachers of English.